Heterologous Expression of Recombinant Human Insulin Glargine (hIG) in Methylotrophic Yeast Pichia pastoris - Herawati, Neng; Rubiyana, Yana; Desriani, Desriani; Santoso, Adi (Annales Bogorienses, 2022)
World health organization (WHO) announced that diabetic patients increased significantly yearly worldwide. Consequently, the need for insulin becomes very large. Pichia pastoris, defined as methylotrophic yeast and a well-known expression and protein production host, is widely used for biopharmaceutical-based drug production. This research aims to synthesize human insulin glargine (hIG) protein in yeast P. pastoris. Human insulin glargine is a group of long-acting analogue insulin.We used a synthetic hIG-encoding gene constructed in frame with the truncated α-factor secretion signal in a pD902 expression vector. Recombinant plasmid pD902-hIG was linearized using Sac1 enzyme and transformed into P. pastoris genome. Multicopy clones were selected on YPDS plates containing Zeocin™ with concentrations of 100; 500; 1,000; and 2,000 µg//mL. Analyses using SDS-PAGE, slot blot, and Western blot showed that recombinant hIG protein had been obtained with a molecular weight of approximately 6,000 Daltons.